Glial-modulating agents for the treatment of pain: protocol for a systematic review. Issue 4 (6th April 2022) - Gilron, Ian; Xiao, Maggie Z X; Balanaser, Marielle; Carley, Meg; Ghasemlou, Nader; Salter, Michael W; Hutchinson, Mark R; Moulin, Dwight E; Moore, R Andrew; Ross-White, Amanda
Abstract : Introduction: Evidence suggests a role for Central nervous system glia in pain transmission and in augmenting maladaptive opioid effects. Identification of drugs that modulate glia has guided the evaluation of glial suppression as a pain management strategy. This planned systematic review will describe evidence of the efficacy and adverse effects of glial-modulating drugs in pain management. Methods and analysis: A detailed search will be conducted on the Cochrane Central Register of Controlled Trials, Medline, and Embase from their inception until the date the final searches are run to identify relevant randomised controlled trials. The reference lists of retrieved studies, as well as online trial registries, will also be searched. English language, randomised, double-blind trials comparing various glial-modulating drugs with placebo and/or other comparators, with participant-reported pain assessment, will be included. Two reviewers will independently evaluate studies for eligibility, extract data and assess trial quality and potential bias. Risk of bias will be assessed using criteria outlined in the Cochrane Handbook for Systematic Review of Interventions . Primary outcomes for this review will include any validated measure of pain intensity and/or pain relief. Dichotomous data will be used to calculate risk ratio and number needed to treat or harm. The quality of evidence will be assessed using Grading of Recommendations Assessment, Development and Evaluation. Ethics and dissemination: This systematic review does not require formal ethics approval. The findings will be disseminated through peer-reviewed publications and conference presentations. PROSPERO registration number: CRD42021262074.